Marriage contracts from Chaucer to the Renaissance stage - Jacobs, Kathryn Elisabeth (University Press of Florida, 2001)
''A fine historic exploration of why marriage treatments in literary texts are transformed between the 14th and 16th centuries. ... This volume has the power and evidence--both historic and textual--to revamp our understanding of crucial texts.